Webtoon: E-comic Based Application to Support the Learning Process in Higher Education - Appelletti Chiara; Valenti Diego; Saresella Mara (Yayasan Adra Karima Hubbi, 2023)
Webtoon is an application that is split from two syllables namely web and cartoon. Webtoon is an application in the form of online-based cartoons or comics which can be enjoyed in the form of a website, by various groups who have the same interests. Webtoon is a service that is provided by presenting many new webtoons or stories that are released continuously according to the schedule that has been targeted by the webtoon authors themselves. Readers can access it with various technologies such as cellphones, laptops, tablets, or computers. The use of the webtoon application also has many fans, especially among teenagers and adults who have an interest. Therefore, webtoons have extraordinary interest. The purpose of this research is based on the use of webtoon applications to support the learning process in universities. The research method used is a descriptive qualitative method with an in-depth discussion related to the material using the webtoon. The research was carried out by direct interviews with students in Asian countries who use the webtoon application. Researchers asked several forms of questions and answered with explanations and reasons for these students related to the material. The results of the research found that the use of the webtoon application has quite an effect on the learning process in tertiary institutions. The weakness in the research was that the researchers did not interview many students, only a few were interviewed and that too were women. It is hoped that future researchers can conduct interviews with many parties in order to get maximum results